Arsenic Pollution Measured with an online Monitoring System using Daphnia - Donat-P Häder; Gilmar S Erzinger (Open Journal of Environmental Biology - Peertechz Publications, 2017)
Arsenic is a common pollutant in many water reservoirs around the world and is the cause of human mortality in many countries. The microcrustacean Daphnia can be cultured easily and is sensitive to many toxic substances including As. This bioindicator is the basis of the Daphniatox instrument which uses computerized image analysis of swimming organisms in real time. Fourteen endpoints are evaluated including motility, swimming velocity, orientation with respect to light or gravity as well as several cell size and form parameters. Using automatic track analysis of a large number of organisms warrants high statistical significance. In a vertical swimming flask Daphnia shows pronounced gravitaxis moving upward and downward while in a horizontal fl ask the organisms swim in random directions. Exposure for up to 72 h to 0 - 10 mg/L NaAsO2 (corresponding to 0 - 77.5 μM As) according to the standard NBR 12713 protocol showed an EC50 value of 5.97 mg/L for motility after an exposure time of 7 h and 4.82 mg/L after 26 h. Comparably, the EC50 value for velocity was 5.32 mg/L after an exposure time of 7 h and after 26 h it was 3.05 mg/L. As expected, the length of the organisms did not change over the exposure time because of their rigid exoskeleton, but the circularity which corresponds to the area divided by the perimeter squared decreased which is interpreted to be due to a release of water. The results indicate that this method provides a reliable, fast and inexpensive test for arsenic toxicity in drinking water from wells and reservoirs.